2015
DOI: 10.1177/1464993414546976
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: A threat to the economic growth of Pakistan

Abstract: Pakistan is recognized as a country with low income along with poor human development indicators. Although its contribution to greenhouse gas (GHG) emissions is miniscule in comparison with other countries (it contributes only about 0.8 per cent of the total GHG emissions), it is one of the major victims of the adverse effects of climate change. The present study is an attempt to explore the impacts of climate change on the economic growth of Pakistan by conducting a national level analysis for the period 1973… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
4
20
0
Order By: Relevance
“…Climate change in the form of increased temperature has reduced cereal yield up to 17% (Lobell et al, 2011). Pakistan is also facing impacts of climate change in different socio-economic sectors (Akram and Hamid, 2015;Ahmad et al, 2017). The warming trend, predicted to be 2-4 • C at the end of century, will drastically affect agriculture (Rasul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change in the form of increased temperature has reduced cereal yield up to 17% (Lobell et al, 2011). Pakistan is also facing impacts of climate change in different socio-economic sectors (Akram and Hamid, 2015;Ahmad et al, 2017). The warming trend, predicted to be 2-4 • C at the end of century, will drastically affect agriculture (Rasul et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This thermal trend has been observed during three decades beginning in the 1980s and predominantly in the 2000s in Punjab, Pakistan (Wang, Davies, Huang, & Gillies, ). The mean surface temperature has shown a slow annual increase that has impacted the socio‐economic sector of Pakistan (Akram & Hamid, ). The observed mean temperature in Punjab, Pakistan, has increased by 0.78–1.5°C for the past three decades and is expected to increase from 2 to 4°C by the end of 21 century, which could have a significant impact on agricultural production (Ahmad et al., ; Mueller, Gray, & Kosec, ; Rasul, Mahmood, Sadiq, & Khan, ).…”
Section: Introductionmentioning
confidence: 99%
“…The GDP and per capita growth lead towards environmental degradation, whereas pandemics and disruption in economic activities have a contrary impact on climate (World Bank 2020 ; das Neves Almeida et al 2017 ; Ali et al 2019 ). Akram ( 2013 ) and Akram and Hamid ( 2015 ) examined the bilateral relationship among GDP, energy consumption, industrial output, and climate change. The outcomes revealed that these factors have caused the temperature to rise in Pakistan and have a detrimental effect on the environment.…”
Section: Literature Reviewmentioning
confidence: 99%